A Scoping Review of the Health of Conflict-Induced Internally Displaced Women in Africa - Amodu, Oluwakemi C. (Int J Environ Res Public Health, 2020)
Armed conflict and internal displacement of persons create new health challenges for women in Africa. To outline the research literature on this population, we conducted a review of studies exploring the health of internally displaced persons (IDP) women in Africa. In collaboration with a health research librarian and a review team, a search strategy was designed that identified 31 primary research studies with relevant evidence. Studies on the health of displaced women have been conducted in South- Central Africa, including Democratic Republic of Congo (DRC); and in Eastern, East central Africa, and Western Africa, including Eritrea, Uganda, and Sudan, Côte d’Ivoire, and Nigeria. We identified violence, mental health, sexual and reproductive health, and malaria and as key health areas to explore, and observed that socioeconomic power shifts play a crucial role in predisposing women to challenges in all four categories. Access to reproductive health services was influenced by knowledge, geographical proximity to health services, spousal consent, and affordability of care. As well, numerous factors affect the mental health of internally displaced women in Africa: excessive care-giving responsibilities, lack of financial and family support to help them cope, sustained experiences of violence, psychological distress, family dysfunction, and men’s chronic alcoholism. National and regional governments must recommit to institutional restructuring and improved funding allocation to culturally appropriate health interventions for displaced women.